The experience of stigma in family caregivers of people with schizophrenia spectrum disorders: A meta-synthesis study. Issue 3 (March 2023) - EghbalManesh, Azadeh; Dalvandi, Asghar; Zoladl, Mohammad
Abstract: Introduction: Schizophrenia is a chronic disabling and the most stigmatizing mental disorder worldwide. The stigma experienced by family caregivers impacts their lives in different ways. This study reports the results of qualitative synthesis to understand the perceptions and experiences of stigma in families of people with schizophrenia spectrum disorders across various socio-cultural contexts. Methods: An initial comprehensive search was performed in databases like Web of Science, PsycINFO, CINAHL, Scopus, and Ovid-based MEDLINE. By searching, 3560 studies were found, of which 16 articles were included in the present study. A meta-synthesis was done according to the meta-ethnographic approach. Result: Three themes were generated: perpetuated stigma by general misunderstandings about schizophrenia, mental health inequality contributes to structural stigma, and long-term family caregiving stigmas, attitudes, and coping strategies. These themes indicated the essential experiences of stigma in families of people with schizophrenia, which appeared due to unknown and socio-cultural misconceptions of schizophrenia that led to emotional challenges for family caregivers. Conclusion: This study addresses stigma-related issues, and coping strategies used almost exclusively by family caregivers. Health policymakers and healthcare professionals working in mental health institutions should consider this data. Substantial steps must be taken to combat stigma, with education initiatives topping the list.